Arsenic mobilization in an oxidizing alkaline groundwater: Experimental studies, comparison and optimization of geochemical modeling parameters. (September 2016) - Hafeznezami, Saeedreza; Lam, Jacquelyn R.; Xiang, Yang; Reynolds, Matthew D.; Davis, James A.; Lin, Tiffany; Jay, Jennifer A.
Abstract: Arsenic (As) mobilization and contamination of groundwater affects millions of people worldwide. Progress in developing effective in-situ remediation schemes requires the incorporation of data from laboratory experiments and field samples into calibrated geochemical models. In an oxidizing aquifer where leaching of high pH industrial waste from unlined surface impoundments led to mobilization of naturally occurring As up to 2 mg L −1, sequential extractions of solid phase As as well as, batch sediment microcosm experiments were conducted to understand As partitioning and solid-phase sorptive and buffering capacity. These data were combined with field data to create a series of geochemical models of the system with modeling programs PHREEQC and FITEQL. Different surface complexation modeling approaches, including component additivity (CA), generalized composite (GC), and a hybrid method were developed, compared and fitted to data from batch acidification experiments to simulate potential remediation scenarios. Several parameters strongly influence the concentration of dissolved As including pH, presence of competing ions (particularly phosphate) and the number of available sorption sites on the aquifer solids. Lowering the pH of groundwater to 7 was found to have a variable, but limited impact (<63%) on decreasing the concentration of dissolved As. The models indicate that in addition to lowering pH, decreasing the concentration of dissolved phosphate and/or increasing the number of available sorption sites could significantly decrease the As solubility to levels below 10 μg L −1 . The hybrid and GC modeling results fit the experimental data well (NRMSE<10%) with reasonable effort and can be implemented in further studies for validation. Highlights: Samples were collected from an oxidizing aquifer where high pH waste has led to mobilization of naturally occurring As. Three surface complexation modeling approaches were used in modeling adsorption of As on aquifer sediments. Modeling tools PHREEQC and FITEQL were employed for developing geochemical models to simulate the experimental data. The hybrid and generalized composite models showed promising results in fitting the experimental data.